On the inelastic torsional response of single storey structures under bi-axial excitation. - Perus, Iztok (Earthquake engineering & structural dynamics.)
An attempt has been made to explore the general trends in the seismic response of plan-asymmetric structures without any restrictions imposed by a particular code. Systems with structural elements in both orthogonal directions under bi-directional excitation wre studied. Idealized single storey models with bi-axial eccentricity were employed. The systems were torsionally stiff and, in the majority of cases, mass-eccentric. The main findings are : in general, inelastic torsional response is qualitatively similar to elastic torsional response. Quantitatively, the torsional effect o the flexible side, expressed as an increase of displacements due to torsion, decreases slightly with increasing plastic deformation, unless the plastic deformations are small. The response on the stiff side generally strongly depends on the effect of several modes of vibration and on the influence of the ground motion in the transverse direction. These influences depend on the structural and ground motion characteristics in both directions. Reduction of displacements due to torsion, typical for elastic torsionally stiff structures, usually decreases with increasing plastic deformations. As an additional effect of large plastic deformations, a flattening of the displacement envelopes in the horizontal plane usually occurs, indicating that torsional effects in the inelastic range are generally smaller than in the elastic range. The dispersion of the results of inelastic torsional response analysis is generally larger than that of elastic analysis.